Has atypical work become typical in Germany? Country case studies on labour market segmentation - Werner Eichhorst; Verena Tobsch (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
This paper gives an overview of the transformation of the German labor market since the mid-1990s with a special focus on the changing patterns of labor market segmentation or dualization of employment in Germany. While labor market duality in Germany can partially be attributed to labor market reforms promoting in particular non-standard forms of employment and allowing for an expansion of low pay, structural changes in the economy as well as strategic choices by employers and social partners also play a prominent role.
Keywords: J21; J31; J58; 330; Germany; non-standard work; low pay; labor market segmentation